Distributions of Ion Density Irregularities and Their Gradients Inside Low‐Latitude Ionospheric Plasma Bubbles Based on C/NOFS Planar Langmuir Probe Data - Emanoel Costa; Patrick A. Roddy; John O. Ballenthin (Space Weather)
Abstract Data from the planar Langmuir probe onboard the Communication/Navigation Outage Forecasting System has been processed, with focus on the: (1) identification of Equatorial Plasma Bubbles located within the eclipse sections of the satellite orbits; (2) subdivision of each Equatorial Plasma Bubble into three sections (West Wall, Center, and East Wall); and (3) statistical analyses of the standard deviations and gradients of ion density data for each section. The statistical distributions resulted from the application of the above processing to structures identified during the years October 1, 2008 to September 30, 2009 (solar minimum conditions) and June 5, 2012 to June 4, 2013 (close to maximum conditions of solar cycle 24). The statistical distributions have also been classified considering all longitudes or three 60° longitude sectors in South America, Africa, India‐Asia, as well as all altitudes of the C/NOFS satellite or the limited range from 650 to 800 km. It will be shown that all the parameters (Equatorial Plasma Bubble sections, solar activity, longitude sector, and altitude range) affect the resulting statistical distributions. Additionally, the probability density functions (pdfs) of ion density gradients for the EPB West Walls, Centers, and East Walls and the South American longitude sector, detected during 2012 and estimated with different resolutions will be compared. While the pdfs based on 1‐Hz low‐resolution data (sampling large‐scale structures) display east‐west asymmetries, those based on the original 512‐Hz high‐resolution data (sampling small‐scale structures), created by secondary plasma instabilities, are essentially symmetric around the reference 0 mm/km gradient.